Analisis dan Perancangan Aplikasi Berbasis Web E-Procurement di PT Pillar Utama Contrindo - Sartika Kurniali; Rudy Rudy; Alex Chandra Wijoyo; Ferdianto Ferdianto; Wendy Wendy (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The aim of this research is to analyze the current business process at the procurement department at PT Pillar Utama Contrindo as well as develop a web based e-procurement application prototype to supportprocurement process at the company. Interview, survey, as well as analysis and design to develop the prototype are used in the research. The research results in an e-procurement application prototype built to minimize errors on related document filling, help the company to get best price on their supply, and increase control. It can be concluded from the research that the protoype can be implemented to be a tool for the users to decide the best supplier, obtain the best price, and increase control in buying process at PT Pillar Utama Contrindo.